IMPLEMENTATION OF SHARIA-BASED FINANCIAL SYSTEM BY OJK: PROMOTING A SUSTAINABLE AND INCLUSIVE ECONOMY - Krisna Rizqi Adi Hibatullah; Naufal Luthfi Ramadhan; Endang Kartini Panggiarti (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
The OJK plays a pivotal role in developing financial products that adhere to Shariah principles, as well as promoting financial inclusion through the expansion of microfinance and the enhancement of the infrastructure and ecosystem of the Shariah financial sector. Furthermore, the OJK actively engages in fostering Shariah financial literacy within the community and collaborates with various stakeholders to improve accessibility to Shariah finance. This article aims to examine the implementation of a Shariah-based financial system by the Financial Services Authority (OJK) with the aim of fostering sustainable and inclusive economic growth. The research methodology employed in this article is qualitative descriptive research, which elucidates the Shariah financial system implemented by the OJK to drive sustainable and inclusive economics. This article underscores the importance of sustainable economic growth and emphasizes the necessity of cooperation between the government, private sector, civil society, and international institutions to achieve these objectives. The OJK assumes a critical role in overseeing and ensuring the compliance of financial institutions with Shariah principles, while also advocating for awareness and understanding of Shariah finance and its associated benefits through educational and training programs. This article highlights the significance of enhancing awareness and understanding of the Shariah-based financial system among Indonesian society, and proposes measures that can be undertaken by the OJK to promote this objective. It underscores the importance of public education and awareness programs aimed at increasing knowledge and appreciation of Shariah finance, thereby contributing to a more sustainable and inclusive economic landscape in Indonesia.